Green Justice: The Case for Establishing a Special Environmental Court in the State of Qatar, Challenges and Alternatives to Promote Environmental Justice - Hayajneh, Abdelnaser Zeyad Ali (Journal of Ecohumanism, 2024)
The State of Qatar is witnessing a state of development at various levels, and is proceeding differently towards achieving the Qatar National Vision 2030, which has four axes: human, social and environmental development. Within the framework of protecting the environment and combating environmental violations, the State of Qatar has issued many environmental legislations and ratified many international environmental agreements, In addition to assigning environmental affairs in the country to a specialized ministry, the Ministry of Environment and Climate Change, there is reason to say that the State of Qatar has achieved distinguished successes in the field of environmental protection and achieving sustainability. However, environmental lawsuits in the State of Qatar are still heard according to the traditional rules of jurisdiction, and the same procedures prescribed for lawsuits of various types, civil, criminal, and administrative. This is because there is no special environmental court or judicial body specialized in environmental lawsuits, as well as the absence of special procedural rules in environmental lawsuits and the implementation of judgments issued therein. This reality does not reflect the special characteristics of environmental lawsuits that requires the presence of a specialized judicial body or procedures and executive rules commensurate with the technical, legal, and economic characteristics of these lawsuits that make it necessary to assess the possibility and visibility of establishing a specialized environmental judiciary within the framework of the existing judicial system. This research will present the case for establishing special environmental judiciary in the State of Qatar. The justifications and requirements for its establishment, as well as the challenges attached to this option. The study will envisage what is required legislatively, administratively, and technically to initiate the establishment of a special system for litigation in environmental lawsuits. The conclude that the establishment of special environmental court will certainly enhance environmental justice in a way that reflects the development of the Qatari legal system, and the leadership of the State of Qatar in various fields, including legal and judicial, and contribute to achieving the country’s National Vision 2030, which made environmental development one of its four pillars.